PHILOSOPHICAL ASPECTS OF THE APPLICATION OF JUSTICE TO DISABLED PERSONS (The Conference Hub, 2025)
This article scientifically studies the philosophical issues of the application of justice to people with social disabilities in society, the possibilities of society to ensure social justice in society, and the formation of a legal framework for social justice in legislation.